Listening to the text oral patterning in Paul's letters - Harvey, John D. 1951- (Grand Rapids, MI Baker, 1998)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Epistles of Paul -- language, style; Rhetorical criticism